2020
DOI: 10.1158/1078-0432.ccr-19-1606
|View full text |Cite
|
Sign up to set email alerts
|

A Combinatorial Strategy for TargetingBRAFV600E-Mutant Cancers with BRAFV600E Inhibitor (PLX4720) and Tyrosine Kinase Inhibitor (Ponatinib)

Abstract: ◥Purpose: Most aggressive thyroid cancers are commonly associated with a BRAF V600E mutation. Preclinical and clinical data in BRAF V600E cancers suggest that combined BRAF and MEK inhibitor treatment results in a response, but resistance is common. One mechanism of acquired resistance is through persistent activation of tyrosine kinase (TK) signaling by alternate pathways. We hypothesized that combination therapy with BRAF and multitargeting TK inhibitors (MTKI) might be more effective in BRAF V600E thyroid c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Hematoxylin and eosin staining demonstrated a reduction of pulmonary metastasis in the vemurafenib treated group and combination treated group. Finally, assays on 8505C resistant to vemurafenib showed that the combination with ponatinib overcomes the acquired resistance [51].…”
Section: Combination To Mapk/mek Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hematoxylin and eosin staining demonstrated a reduction of pulmonary metastasis in the vemurafenib treated group and combination treated group. Finally, assays on 8505C resistant to vemurafenib showed that the combination with ponatinib overcomes the acquired resistance [51].…”
Section: Combination To Mapk/mek Inhibitorsmentioning
confidence: 99%
“…Vemurafenib is a mutant BRAF inhibitor and it is one of these molecules that are failing in clinical assays as monotherapy [52]. In vitro studies have been conducted to elucidate resistance mechanisms but reasons explaining the higher resistance observed of thyroid BRAFV600E mutant thyroid cancer in comparison to melanoma to BRAF inhibitor remains unclear [51]. Compensatory/alternative mechanisms have been highlighted to promote such resistance, bypassing pharmacologic inhibition of BRAFV600E via the activation of intracellular signaling pathways, leading to the reactivation and phosphorylation of ERK1/2, NRAS mutation, mutant BRAF amplification, or alternative splicing [51].…”
Section: Mapk and Pi3k Inhibitors Used As Single Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, 10 days after venetoclax initiation, the patient was admitted with neutropaenic fever and tumour lysis syndrome (TLS), requiring a hold on his therapy. Vemurafenib, an FDA‐approved BRAF V600E inhibitor, 9 was initiated based on the molecular results, at a dose of 960 mg PO Q12. Receiving a total of 20 days of therapy, the patient had improvement in renal function and WBC count.…”
Section: Figurementioning
confidence: 99%